2022
DOI: 10.1021/acsami.2c08691
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach to High κ (∼59) and Low EOT (∼3.8 Å) near the Morphotrophic Phase Boundary with AFE/FE (ZrO2/HZO) Bilayer Heterostructures and High-Pressure Annealing

Abstract: We present herewith a novel approach of equally thick AFE/FE (ZrO2/HZO) bilayer stack heterostructure films for achieving an equivalent oxide thickness (EOT) of 4.1 Å with a dielectric constant (κ) of 56 in complementary metal-oxide semiconductor (CMOS) compatible metal–ferroelectric–metal (MFM) capacitors using a high-pressure annealing (HPA) technique. The low EOT and high κ values were achieved by careful optimization of AFE/FE film thicknesses and HPA conditions near the morphotropic phase boundary (MPB) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 50 publications
(116 reference statements)
0
7
0
Order By: Relevance
“…Moreover, a leakage current density lower than <10 –7 A/cm 2 was observed at 0.8 V, which is the standard requirement for DRAM cell capacitors. The enhanced electrical properties of the bilayer systems compared with those of the single-layer capacitors likely originated from the small grain size of the ZrO 2 /Hf 0.5 Zr 0.5 O 2 bilayer fabricated by a high-pressure annealing technique . However, several issues must be resolved before realizing practical DRAM applications.…”
Section: Applications Of Fluorite-structured Antiferroelectricsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a leakage current density lower than <10 –7 A/cm 2 was observed at 0.8 V, which is the standard requirement for DRAM cell capacitors. The enhanced electrical properties of the bilayer systems compared with those of the single-layer capacitors likely originated from the small grain size of the ZrO 2 /Hf 0.5 Zr 0.5 O 2 bilayer fabricated by a high-pressure annealing technique . However, several issues must be resolved before realizing practical DRAM applications.…”
Section: Applications Of Fluorite-structured Antiferroelectricsmentioning
confidence: 99%
“…Copyright 2018 ACS Publications. (b) Reprinted with permission from ref . Copyright 2020 ACS Publications.…”
Section: Applications Of Fluorite-structured Antiferroelectricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important issue that arises with the decrease in the physical thickness of the ferroelectric HZO film is the increase in the leakage current density. Figure b illustrates the changes in leakage current density as a function of equivalent oxide thickness (EOT) of HfO 2 , ZrO 2 , and HZO thin films . From Figure b, it can be observed that the leakage current density increases as the film thickness decreases, and this trend intensifies, particularly when the EOT falls below 0.8 nm.…”
mentioning
confidence: 95%
“…(b) Current density ( J ) at 0.8 V as a function of equivalent oxide thickness (EOT) for ZrO 2 , HZO, and ZrO 2 /HZO bilayer. Reproduced with permission from ref . Copyright 2023 American Chemical Society.…”
mentioning
confidence: 99%